2002
DOI: 10.1116/1.1464840
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of ultrahigh vacuum/chemical vapor deposition SiGe epitaxial layers on bulk single-crystal SiGe and Si substrates

Abstract: Momentum space tomographic imaging of photoelectrons AbstractWe apply tomography, a general method for reconstructing 3D distributions from multiple projections, to reconstruct the momentum distribution of electrons produced via strong field photoionization. The projections are obtained by rotating the electron distribution via the polarization of the ionizing laser beam and recording a momentum spectrum at each angle with a 2D velocity map imaging spectrometer. For linearly polarized light, the tomographic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Traditionally, MOS transistors are built on bulk Si substrates. However, recent studies [6][7][8] have shown that strained Si epilayers grown on a relaxed Ge-Si substrate can significantly increase the dopant mobility in Si and so the operating speed and frequency of Si devices. In fact, these Ge-Si substrates are virtual substrates in the sense that they are grown as epilayers on Si substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, MOS transistors are built on bulk Si substrates. However, recent studies [6][7][8] have shown that strained Si epilayers grown on a relaxed Ge-Si substrate can significantly increase the dopant mobility in Si and so the operating speed and frequency of Si devices. In fact, these Ge-Si substrates are virtual substrates in the sense that they are grown as epilayers on Si substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk Ge-Si substrates stand as a strong substitute for virtual Ge-Si substrates. Recently, there have been studies [8][9][10] demonstrating that Ge-Si substrates grown using the bulk crystal growth techniques may have several advantages over the virtual substrates. In addition, compositionally graded bulk grown Ge-Si alloys have been successfully used in X-ray, g-ray, and neutron-diffraction optics [11,12].…”
Section: Introductionmentioning
confidence: 99%